Adaptive vector control of PV-fed induction motor using boost split-source inverter without MPPT - Romaissa Hamdi; Yassine Beddiaf; Djamel Sakri; Daoud Rezzak; Hassina Slimani (Indonesian Journal of Electrical Engineering and Computer Science, 2026)
This paper proposes an adaptive vector control strategy for a photovoltaic (PV)-fed induction motor using a boost split-source inverter (BSSI). Unlike conventional PV conversion systems, the proposed topology combines voltage boosting and DC–AC conversion in a single stage, reducing component count, switching losses, and overall system complexity. In addition, the system operates without a maximum power point tracking (MPPT) algorithm, simplifying the control structure while maintaining stable operation under varying environmental conditions. The proposed control approach integrates sliding mode control (SMC) for robust DC-bus voltage regulation and an adaptive proportional–integral (API) speed controller based on Lie derivative theory for online tuning of controller gains according to the speed tracking error. An active DC-link protection mechanism is also introduced to prevent overvoltage during transient conditions. The main contribution of this paper lies in the combination of the BSSI topology with a hybrid adaptive control framework to improve robustness, dynamic performance, and system reliability under irradiance, temperature, and load variations. Simulation and experimental results demonstrate fast dynamic response, reduced speed and voltage oscillations, accurate speed tracking, and superior performance compared with conventional vector control methods.